2022
DOI: 10.31039/jgss.v3i11.88
|View full text |Cite
|
Sign up to set email alerts
|

Impact of capital market performance on economic growth: An assessment from Nigeria

Abstract: This is an investigation of the impact of capital market performance on economic growth in Nigeria from 2010 to 2020. The general objectives were to assess the impact of market capitalisation on Real GDP, to determine the influence of the value of trade on Real GDP. Ordinary least square (OLS) method was used for estimation to evaluate the impact of capital market performance on economic growth in Nigeria using secondary quarterly times series data from Q1 2010 to Q4 2020. Data was obtained from Nigeria Stock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…While recently, bibliographic databases have become leading providers of publication metadata for research assessment [9,20] and research grants performance and monitoring [29,30], our study implies that selecting the only one of these databases might produce misleading results. For example, a funding agency might evaluate their impact by analyzing the number of FAs in publications and over or underestimate the impact by selecting the wrong database.…”
Section: Discussionmentioning
confidence: 87%
“…While recently, bibliographic databases have become leading providers of publication metadata for research assessment [9,20] and research grants performance and monitoring [29,30], our study implies that selecting the only one of these databases might produce misleading results. For example, a funding agency might evaluate their impact by analyzing the number of FAs in publications and over or underestimate the impact by selecting the wrong database.…”
Section: Discussionmentioning
confidence: 87%
“…Liquidity for all securities issued by the government and different corporate entities is provided by the market. In this market, investors have the option to convert their cash holdings in securities into other securities for investing purposes or related goals (Odo, Anoke, Onyeisi, & Chukwu 2017).The secondary market is "a value for providing liquidity to investors," according to Umar (2022). On the six trading floors of the Nigerian Capital Exchange, licensed stockbrokers call out secondary market transactions in quoted securities.…”
Section: The Secondary Marketmentioning
confidence: 99%
“…The financial system's capital market is a crucial component that offers an effective means of distributing, managing, and allocating long-term capital (Umar, 2022;Yakubu, 2023). The longterm loan market is where they are transacted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some existing studies have shown that exchange rate instability, high lending interest rate, as well as, hostility measures on border closure policies worsen the stock market integration Oprea and Stoica, 2018). Aside from this, research has shown that corporate investments can reduce the high levels of poverty that are impacting developing countries negatively by making household engages in productive activities through provision of employment opportunities that put individual household in better position to afford basic needs of life (Okafor et al, 2021;Umar, 2022). Given this, the present study critically appraises the effect of stock market integration on corporate investment in Nigeria from 1986-2022.…”
Section: Nejo Femi Michaelmentioning
confidence: 99%